The Reality of Guidance and Counseling Services Implementation at SMAN 1 Lemahabang - Denissa Aulia Ramadhan; Ega Najwa Ismail; Ellsya Endany Anie Ramadhani; Yusriya Ni’matul’Izzah; Nur Aini Farida (Penerbit Hellow Pustaka, 2025)
This study aims to describe the reality of implementing Guidance and Counseling (GC) services at SMAN 1 Lemahabang, covering the types of services, their conformity with national standards, and the supporting and inhibiting factors. The research employed a qualitative descriptive approach through observation and interviews with the counseling teacher and three twelfth-grade students. The results show that the GC services at SMAN 1 Lemahabang cover four main areas personal, social, learning, and career, and are in line with the Ministry of Education Regulation No. 111 of 2014. Supporting factors include strong support from the principal, teacher collaboration, and active student participation. However, the main obstacle lies in the limited number of counselors, with one teacher serving approximately 545 students, resulting in less optimal individual guidance. Nevertheless, the counselor optimizes services through group approaches, cooperation with Islamic Education teachers in character development, and the use of online communication media. The study emphasizes the need to increase the number of counselors and strengthen collaborative systems to make GC services more effective and responsive to students’ needs.